A Dynamic Theory of Interfirm Behavior - Williamson, Oliver E. (Quarterly Journal of Economics, 1965)
Introduction, 579. — I. A gross description, 580. — II. A dynamic model, 582; the interfirm relationships, 582; a differential equations model, 585; proposed measurements, 594. — III. Extensions, 595; a self-recovery mechanism, 596; the influence of structure, 599; the effects of regulatory restraint, 603.— IV. Conclusions, 606.